Long-term outcome and risk factors for late mortality in Gram-negative bacteraemia: a retrospective cohort study. (June 2021) - Baltas, Ioannis; Stockdale, Thomas; Tausan, Matija; Kashif, Areeba; Anwar, Javeria; Anvar, Junaid; Koutoumanou, Eirini; Sidebottom, David; Garcia-Arias, Veronica; Wright, Melanie; Democratis, Jane
Highlights: 36.2% of patients died 1 year after an episode of Gram-negative bacteraemia. One-half of these patients suffer late mortality at 31–365 days after detection of infection. An adverse resistance profile and P. aeruginosa infection constitute independent risk factors for late mortality. ABSTRACT: Objectives: The long-term outcomes of patients following Gram-negative bacteraemia (GNB) are poorly understood. Here we describe a cohort of patients with GNB over a 2-year period and determine factors associated with late mortality (death between Days 31 and 365 after detection of bacteraemia). Methods: This was a single-centre, retrospective, observational cohort study of 789 patients with confirmed Escherichia coli, Klebsiella spp. or Pseudomonas aeruginosa bacteraemia with a follow-up of 1 year. Multivariable survival analysis was used to determine risk factors for late mortality in patients who survived the initial 30-day period of infection. Results: Overall, 1-year all-cause mortality was 36.2%, with 18.1% of patients dying within 30 days and 18.1% of patients suffering late mortality. An adverse antimicrobial resistance profile [hazard ratio (HR) = 1.095 per any additional antimicrobial category, 95% confidence interval (CI) 1.018–1.178; P  = 0.014] and infection with P. aeruginosa (HR = 2.08, 95% CI 1.11–3.88; P  = 0.022) were independent predictors of late mortality. Other significant factors included Charlson comorbidity index and length of hospitalisation after the index blood culture. Conclusion: Patients with GNB have a poor long-term prognosis. Risk factors for greater mortality at 1 year include co-morbidity, length of hospitalisation, and infecting organism and its resistance profile.